2018
DOI: 10.1002/jia2.25177
|View full text |Cite
|
Sign up to set email alerts
|

A Commitment to HIV Diagnostic Accuracy – a comment on “Towards more accurate HIV testing in sub‐Saharan Africa: a multi‐site evaluation of HIV RDTs and risk factors for false positives” and “HIV misdiagnosis in sub‐Saharan Africa: a performance of diagnostic algorithms at six testing sites”

Abstract: As part of the global response to the HIV/AIDS epidemic, the U.S. President's Emergency Plan for AIDS Relief (PEPFAR) is committed to the provision of high‐quality services and ensuring testing accuracy. Two recently published papers focusing on HIV testing and misdiagnosis in sub‐Saharan Africa by Kosack et al. report on evaluations of HIV rapid diagnostic tests (RDTs) and found lower than expected specificity and sensitivity on some tests when used in certain geographic locations. The magnitude of PEPFAR's g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…And, retesting can rule out possible technical or clerical errors, including specimen mix-up through mislabeling and transcription errors, as well as random error by either the provider or the test device, though retesting for verification will not exclude misdiagnosis related to poor choice of a testing algorithm or cross-reactivity[18]. However, this risk should be reduced assuming the testing algorithm used is validated[20, 69, 70]. The WHO recommends following the approved national HIV testing algorithm and ensuring adherence to a quality-testing program with continuous quality assurance.…”
Section: Resultsmentioning
confidence: 99%
“…And, retesting can rule out possible technical or clerical errors, including specimen mix-up through mislabeling and transcription errors, as well as random error by either the provider or the test device, though retesting for verification will not exclude misdiagnosis related to poor choice of a testing algorithm or cross-reactivity[18]. However, this risk should be reduced assuming the testing algorithm used is validated[20, 69, 70]. The WHO recommends following the approved national HIV testing algorithm and ensuring adherence to a quality-testing program with continuous quality assurance.…”
Section: Resultsmentioning
confidence: 99%
“…Analytical validation of the manufacturers is usually performed with serum panels from people that do not always coincide with the target population. These serum panels are from populations who may not have diversity in the antigenic exposure ( T. cruzi strains), variations in population genetic bases of immune response, cross-reactivity with other prevalent infections, or differences in the samples used ( 28 , 29 ). For this reason, prior to the implementation of an RDT in the routine protocols, it is recommended to perform a verification study of the parameters indicated by the manufacturer in the target population.…”
Section: Discussionmentioning
confidence: 99%
“…The recommendation for verification of HIV status before ART initiation has been increasingly adopted to ensure the fidelity of the HIV testing and ART programmes and avoid future costs and ramifications associated with inadvertently initiating HIV‐negative persons on lifelong ART. Previous studies have highlighted that retesting may be particularly important considering reports of poor quality testing and low uptake of WHO‐recommended HIV testing strategies and algorithms . Policy analysis from 2015 suggested fewer than 20% of reporting countries had a national testing strategy and algorithm that was in full alignment with WHO guidelines .…”
Section: Discussionmentioning
confidence: 99%
“…These efforts combined with updated guidelines and re‐training of testers, decreased HIV‐negative test results following an initial HIV‐positive diagnosis from 7% to 1% between 2014 and 2016 . Additional studies have highlighted the role of retesting, alongside validation of national algorithms, to ensure quality .…”
Section: Discussionmentioning
confidence: 99%